Water Quality Control at the Tirta Tarum Regional Drinking Water Public Company to Improve Services to the Community - Trisna Mukti, Aditya; Nindiani, Aina; Roban, Roban (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Water is a fundamental necessity for human life, and access to clean water is essential. Drinking water must meet health standards to be safe for consumption, while clean water is used for daily needs and can be consumed if boiled. However, consumer complaints regarding water quality remain a concern. Data collected over a three-month period indicated that the average turbidity level of clean water was 2.4 NTU. This study aims to control water quality using the Taguchi method. The key objective is to evaluate whether the water quality complies with established standards and regulatory requirements. Water quality that meets these standards is expected to enhance customer satisfaction. By applying the Taguchi experimental design, the results demonstrated a turbidity level of 1.4 NTU and a pH level of 7.3, both of which comply with the Ministry of Health Regulation No. 2 of 2023. The findings suggest that implementing quality control through the Taguchi method can effectively monitor and regulate water quality, thereby improving water services provided to the community.